2003
DOI: 10.1902/jop.2003.74.5.603
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Incadronate on the Progression of Rat Experimental Periodontitis by Porphyromonas gingivalis Infection

Abstract: These results showed that incadronate inhibits bone resorption and PMN migration in P. gingivalis-induced periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…Alencar et al 11 analyzed the preventive and healing effects of subcutaneous disodium chlodronate in rats with experimental periodontitis and found that high doses inhibit bone loss. Another study on experimental periodontitis by Porphyromonas gingivalis infection in rats showed that oral administration of incadronate prevents bone loss and the migration of polymorphonuclear neutrophil leukocytes (PMNs) 27 …”
Section: Discussionmentioning
confidence: 99%
“…Alencar et al 11 analyzed the preventive and healing effects of subcutaneous disodium chlodronate in rats with experimental periodontitis and found that high doses inhibit bone loss. Another study on experimental periodontitis by Porphyromonas gingivalis infection in rats showed that oral administration of incadronate prevents bone loss and the migration of polymorphonuclear neutrophil leukocytes (PMNs) 27 …”
Section: Discussionmentioning
confidence: 99%
“…2,34 Most pharmacological attempts to control bone loss have focused on inhibiting bone resorption. [3][4][5][6] The induction of a formative reaction to restore destroyed bone, appeared beyond reach. RG1503 treatment introduces a new paradigm, as it targets both aspects of bone balance.…”
Section: Rg1503 Treatment Rebuilds Lost Alveolar Bonementioning
confidence: 99%
“…The most generalized form of destruction, horizontal bone loss, cannot be reversed by current therapies. Strategies based on chemical disease control can stabilize disease progress [3][4][5][6] but are unable to rebuild the lost tissues. Comprehensive treatment for periodontitis should include the control of gingival inflammation that fuels bone loss, inhibition of osteoclastic resorption, and stimulation of bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies demonstrated a reduction of radiological and/or clinical signs of PD, including alveolar bone loss, gingival index and bleeding [8], [9], [10], [11], [12]. These beneficial effect of bisphosphonates on mandibular bone loss have also been demonstrated in animal models of PD such as the rice rat [13], [14], and/or as induced by elastic rings [15], [16], tooth ligature [7], [17], and bacterial inoculations [18], [19].…”
Section: Introductionmentioning
confidence: 99%